The Field of Cell Competition Comes of Age: Semantics and Technological Synergy - Maheden, Kieran; Zhang, Vivian Weixuan; Shakiba, Nika (Frontiers in Cell and Developmental Biology, 2022)
Stem cells experience many selective pressures which shape their cellular populations, pushing populations to skew towards dominance of a few break-through clones. An evolutionarily conserved answer to curb these aberrant selective pressures is cell competition, the elimination of a subset of cells by their neighbours in a seemingly homogenous population. Cell competition is a relatively recent discovery that has now been seen in many tissue systems, such as embryonic, haematopoietic, intestinal, and epithelial. With this rapidly growing field, there is a need to revisit and standardize the terminology used, much of which has been co-opted from evolutionary biology. Further, the information flow between biological scales involved in cell competition can be difficult to interpret. In this review, we make two key points. One, we propose new nomenclature to standardize concepts across dispersed studies of different types of competition, each of which currently use the same terminology to describe different phenomena. Second, we challenge the field to incorporate next generation technologies into the standard cell competition toolkit, as this will help bridge information flow across biological scales. This has been lacking in the field and is particularly key to unraveling mechanisms of cell competition, given that molecular events shape cellular growth and death dynamics that compose our tissues, ultimately experiencing evolutionary pressures at the organism level.